Penerapan Fungsi Staffing Dalam Mencapai Tujuan Pendidikan - Septiandy, Muhammad Fichri; Arizki, Aqsol; Harahap, Wahit Gunadi; Nasution, Yudha Akbar (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This article discusses the application of the staffing function in achieving educational goals. The main focus is the placement of quality human resources and development of administrative staff to support school operations. Through the implementation of appropriate staffing, this journal emphasizes the importance of aligning human resource competencies with educational needs. Apart from that, the role of employees is also considered to ensure that each individual supports the effectiveness of learning. Thus, this journal highlights the relevance of implementing the staffing function in achieving educational goals. This article also describes the meaning of staffing in educational administration, principles of staffing, and staffing functions which consist of human resource planning, recruitment, selection, education and training, placement and dismissal of personnel. The methodology applied in preparing this article uses a qualitative descriptive approach and uses literature study methods so that it can describe data found from various sources such as books, scientific journals, research papers and other supporting sources.